DRAMATURGY REQUIREMENTS IN ARISTOTLE'S “POETICS” (World Bulletin of Social Sciences, 2024)
term “artistic” is derived from the Arabic words “bad'un” and "bade'a" - meaning to innovate, create, create, invent, discover. This term refers to the most primary, leading concept of art forms that follow the laws of beauty.